Simulating the impacts of credit policy and fertilizer subsidy on Central Luzon rice farms, the Philippines - Rosegrant, Mark W.; Herdt, Robert W. (Wiley, 1981)
The effects of credit policy and fertilizer subsidy on farmers' input choices, production, and income are examined with a multiseason decision‐making model. Stochastic production technology, risk‐neutral and risk‐averse decision rules, short‐term savings/consumption behavior, and a dual financial market are considered. Results indicate the risk‐neutral rule is more consistent with actual choices than risk‐averse rules. Estimated yields increased 21% to 30% from joint credit and fertilizer subsidies. Benefits are greater on irrigated than on rainfed farms. A substantial default rate in the institutional market reduces credit program benefits.